LANGUAGE FUNCTION FROM BALINESE DAILY CONVERSATIONS - I Dewa Ayu Devi Maharani Santika; Anak Agung Ayu Dian Andriyani; Ida Bagus Gde Nova Winarta (Language and Education Journal Undiksha, 2022)
Language is not merely as a tool of communication, but it has certain function to build a communication or deliver the purpose of the speaker. People usually do not recognize the function they use from a language. Therefore, this is an interesting topic to be conducted in order to help the readers understand any language function they might use during communication. This study aimed to analyse the language functions taken from some daily conversations in Balinese language of a village in Klungkung regency, Bali. The participants of the conversations are from various social background. The data were collected by using univolved direct conversation with some techniques: observation, note-taking and recording. The theory of Leech (1981) about language function types was used to do the analysis. The result shows that Directive function becomes the most function applied in the conversations. This is because the participants of the conversations often produce the conversation by giving orders or requesting. Meanwhile the function that does not commonly appear is Aesthetic. The reason is these participants often speak straight to the point and almost never try to beautify the utterances they spoke.